On series connection of infinitely many RLC two-ports. Issue 1 (March 2016) - Feintuch, Avraham; Francis, Bruce
Abstract In this paper we study the asymptotic behaviour of infinite systems of first- and second-order linear differential equations arising from the series connection of infinitely many identicalRLC two-ports. These systems exhibit nearest-neighbour dynamics that arise in many aspects of classical and modern physics. We study both the "no capacitor" case, which is a first-order system, and the second-order systems that correspond to damped and undamped oscillators.